Lisbon and its port: urban planning and surveillance expectations and results - Pinheiro, M. (Portuguese Journal of Social Science, 2018)
The rapid urban growth had a strong impact on the living conditions of the inhabitants of the cities. Port Cities experienced significant urban growth in the nineteenth century and early twentieth century. Trade growth and technological changes in ships led to the construction of new port facilities that completely transformed the landscape of port cities. Portuguese governments hoped that the modernization of the port and the establishment of railways would enable transformation of Castile into a hinterland of the Lisbon port. Emerging problems in the early stages of this process were related to hygiene, traffic, safety and the urban image of the city. Due to their relations with the outside world, the impact of migration and the existence of a fluid labour population, port cities sometimes had the image of being dangerous and unsafe havens. It was difficult to survey the flows of population and to control for goods, people and diseases. The aims of this article are to assess the way in which Lisbon and its port followed this international path and to highlight why its actualization was far behind the authorities’ expectations.